2022
DOI: 10.1080/21655979.2022.2050481
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of astragalus polysaccharide by ultrasound microbubbles attenuate doxorubicin-induced cardiomyopathy in rodent animals

Abstract: The aim of this study was to investigate the cardioprotective effects and probable mechanism of ultrasound-targeted microbubble destruction (UTMD) combined with astragalus polysaccharide (APS) on diabetic cardiomyopathy (DCM) model rats. The DCM rats with diabetes and cardiomyopathy were induced via chronic treatment of doxorubicin and then randomly divided into the (1) DCM model group; (2) APS microbubble group; (3) UTMDgroup; and (4) APS microbubbles combined with UTMD group. After 4-week intervention, the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…It was found that DOX can cause mitochondrial dysfunction by acting on PPAR, activating oxidative stress and inflammation and ultimately inducing apoptosis. On the one hand, DOX can reduce the expression of PPAR by regulating Sirt1 or AMPK and further upregulate NF-κB expression, promote inflammatory factor release and aggravate the inflammatory response [120]. On the other hand, DOX can decrease Nrf2 expression by inhibiting PPAR, reduce the level of antioxidant enzymes and reduce the body's antioxidant capacity, resulting in oxidative stress [121].…”
Section: Sirt1/ppar/pgc-1α Signaling Pathwaymentioning
confidence: 99%
“…It was found that DOX can cause mitochondrial dysfunction by acting on PPAR, activating oxidative stress and inflammation and ultimately inducing apoptosis. On the one hand, DOX can reduce the expression of PPAR by regulating Sirt1 or AMPK and further upregulate NF-κB expression, promote inflammatory factor release and aggravate the inflammatory response [120]. On the other hand, DOX can decrease Nrf2 expression by inhibiting PPAR, reduce the level of antioxidant enzymes and reduce the body's antioxidant capacity, resulting in oxidative stress [121].…”
Section: Sirt1/ppar/pgc-1α Signaling Pathwaymentioning
confidence: 99%
“…Liu et al . have reported that diabetes can lead to oxidative stress mediated myocardial fibrosis, and eventually cardiac dysfunction in the diabetic rat model, which plays an important role in the occurrence of diabetes cardiomyopathy [ 24 ]. Moreover, it has been reported in the literature that inhibiting inflammatory response and improving the immune microenvironment of myocardial tissue can alleviate cardiac dysfunction caused by diabetes [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…135 APSs can protect diabetic cardiomyopathy (DCM) rats from myocardial injury and aging by activating the AMPK signaling pathway, reducing myocardial tissue inflammation and oxidative stress. 136 Both raw and honey-processed PSPs inhibited pulmonary inflammation through the NF-κB pathway and reduced the occurrence of pulmonary oxidative stress through the AMPK−Nrf2 pathway. 137 4.7. p53 Signaling Pathway.…”
Section: Insulin/insulin-like Growth Factor-1 (Insulin/igf-1) Signali...mentioning
confidence: 99%
“…ArMPs reduce brain cell apoptosis and neurological deficits by activating the PI3K/AKT/mTOR signaling pathway and its downstream apoptotic protein family . APSs can protect diabetic cardiomyopathy (DCM) rats from myocardial injury and aging by activating the AMPK signaling pathway, reducing myocardial tissue inflammation and oxidative stress . Both raw and honey-processed PSPs inhibited pulmonary inflammation through the NF-κB pathway and reduced the occurrence of pulmonary oxidative stress through the AMPK–Nrf2 pathway …”
Section: Antiaging Targets and Signal Pathways Of Polysaccharidesmentioning
confidence: 99%